KERUSAKAN TEGAKAN DAN LIMBAH PEMANENAN HUTAN RAWA PADA KAWASAN SUATU PERUSAHAAN HUTAN DI KALIMANTAN BARAT - Jumalis Thaib (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
An investigation was carried out at one swamp forest company in West Kalimantan. Timber stand conditions indi cated by the diameter of tree felled all of wich were dominant tree species and the density of all tree species having diameter of 20 cm and up are as follows: the diameter ranging from 39, 7 to 62,2 cm with an average of 51,0 cm while the timber density ranging from 89 to 164 trees with an average of 127 trees per hectare.By felling one tree for harvesting purpose, it caused residual stand damages between 0,35 and 1, 7.1 trees with an average of 1,04 trees. This large range was caused not only by the distribution of timber stand but also by inappropriate felling directions. Logging waste that consisted of stump, clear bole, branch and victimized trees with the diameter o/ 10 cm and up were 0,10 m3 (2 %), 0,80 m3 (19 %), 0,16 m3 (4 %) and 0,49 m3 (12%), respectively. These wastes Cx n be utilized in the future because the output of processing industry is sawn timber only and the location of log resources area is closed to the saw mill site.